2009
DOI: 10.1186/1743-422x-6-197
|View full text |Cite
|
Sign up to set email alerts
|

Anti-viral properties and mode of action of standardized Echinacea purpurea extract against highly pathogenic avian Influenza virus (H5N1, H7N7) and swine-origin H1N1 (S-OIV)

Abstract: BackgroundInfluenza virus (IV) infections are a major threat to human welfare and animal health worldwide. Anti-viral therapy includes vaccines and a few anti-viral drugs. However vaccines are not always available in time, as demonstrated by the emergence of the new 2009 H1N1-type pandemic strain of swine origin (S-OIV) in April 2009, and the acquisition of resistance to neuraminidase inhibitors such as Tamiflu® (oseltamivir) is a potential problem. Therefore the prospects for the control of IV by existing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 27 publications
7
105
0
3
Order By: Relevance
“…Since many traditional medicinal plants have been reported to have strong antiviral activity [6,30,37], they offer a rich source for discovering novel antiviral compounds. In order to explore novel active compounds against IAV, we screened a number of natural compounds purified from different Chinese medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Since many traditional medicinal plants have been reported to have strong antiviral activity [6,30,37], they offer a rich source for discovering novel antiviral compounds. In order to explore novel active compounds against IAV, we screened a number of natural compounds purified from different Chinese medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the actions of Echinaforce should be manifest during initial contact with the virus, that is, at the inception of infection, and also during transmission of virus from infected cells. Additional experiments showed that continuous passage of influenza A virus in cell cultures in the presence of EF did not result in the emergence of resistant strains, whereas in contrast, passing the virus through successive cultures in the presence of Tamiflu rapidly produced Tamiflu-resistance (Pleschka et al, 2009). Furthermore, Tamiflu-resistant virus remained fully susceptible to EF.…”
mentioning
confidence: 99%
“…Recent detailed studies with the standardized preparation Echinaforce  (EF, comprising ethanol extracts of E. purpurea, 95% aerial parts plus 5% roots) revealed that this preparation was very active as a virucidal agent against several viruses with membranes, as indicated in Table 1. In addition to HSV-1 and respiratory syncytial virus, all tested human and avian strains of influenza A virus, as well as influenza B virus, were susceptible (Sharma et al, 2009a;Pleschka et al, 2009). In addition, rhinoviruses were also equally susceptible at the relatively high concentrations of EF recommended for oral consumption (Table 1).…”
mentioning
confidence: 99%
“…Antiviral activity of some medicinal plants against influenza viruses such as green tea, pomegranate, licorice root, milk thistle, Echinacea purpurea, have been reported previously due to the safety and development of resistance by influenza viruses [9,25,30,32]. In the present study, for the first time the researchers demonstrated that lemon balm essential oil ingredients inhibit AVI (H9N2) proliferation and mechanism action of MOEO against AIV was evaluated at different steps of influenza virus replication cycle.…”
Section: Discussionmentioning
confidence: 72%